Intervening to eliminate the centre-effect variation in home dialysis use: protocol for Inter-CEPt—a sequential mixed-methods study designing an intervention bundle - Sarah Damery; Kerry Allen; Lisa Dikomitis; Harry Hill; David Coyle; Maatla Tshimologo; Mark Lambie; Simon J Davies; Iestyn Williams; James Fotheringham; Louise Phillips-Darby; Ivonne Solis-Trapala (BMJ Open)
Introduction Use of home dialysis by centres in the UK varies considerably and is decreasing despite attempts to encourage greater use. Knowing what drives this unwarranted variation requires in-depth understanding of centre cultural and organisational factors and how these relate to quantifiable centre performance, accounting for competing treatment options. This knowledge will be used to identify components of a practical and feasible intervention bundle ensuring this is realistic and cost-effective.Methods and analysis Underpinned by the non-adoption, abandonment, scale-up, spread and sustainability framework, our research will use an exploratory sequential mixed-methods approach. Insights from multisited focused team ethnographic and qualitative research at four case study sites will inform development of a national survey of 52 centres. Survey results, linked to patient-level data from the UK Renal Registry, will populate a causal graph describing patient and centre-level factors, leading to uptake of home dialysis and multistate models incorporating patient-level treatment modality history and mortality. This will inform a contemporary economic evaluation of modality cost-effectiveness that will quantify how modification of factors facilitating home dialysis, identified from the ethnography and survey, might yield the greatest improvements in costs, quality of life and numbers on home therapies. Selected from these factors, using the capability, opportunity and motivation for behaviour change framework (COM-B) for intervention design, the optimal intervention bundle will be developed through workshops with patients and healthcare professionals to ensure acceptability and feasibility. Patient and public engagement and involvement is embedded throughout the project.Ethics and dissemination Ethics approval has been granted by the Health Research Authority reference 20-WA-0249. The intervention bundle will comprise components for all stake holder groups: commissioners, provider units, recipients of dialysis, their caregivers and families. To reache all these groups, a variety of knowledge exchange methods will be used: short guides, infographics, case studies, National Institute for Health and Care Excellence guidelines, patient conferences, ‘Getting it Right First Time’ initiative, Clinical Reference Group (dialysis).